Analisis Tes HIV dengan Sikap Ibu Hamil dalam Pencegahan Penyakit HIV/AIDS di Wilayah Kerja UPT Puskesmas Stabat Lama Tahun 2018 - Aida Fitria; Siti Aisyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The risk of HIV transmission from mother to child without prevention or intervention efforts ranges from 20-50%. Taking an HIV test during pregnancy is an important activity carried out in an effort to increase public awareness about HIV and AIDS.  The purpose of this study was to determine the analysis of HIV testing with the attitudes of pregnant women in the prevention of HIV / AIDS in the Work Area of the Stabat Lama Health Center UPT in 2018. The type of research used is analytic survey with cross sectional approach. The population in this study is the same as the sample taken by accidental sampling as many as 30 people. Data collection methods are primary, secondary and tertiary data. Data analysis used is using univariate and bivariate analysis with chi-square test. The results HIV testing has a relationship with the attitude of pregnant women in the prevention of HIV / AIDS. The conclusion of this study shows that HIV testing has a relationship with the attitudes of pregnant women in HIV / AIDS prevention in the Work Area of the Stabat Lama Health Center UPT in 2018. It is hoped that the research sites can be a reference for the community and for cadres better understand the importance of implementing HIV / AIDS tests for pregnant women.